Relationship between A2A Adenosine Receptor Expression and Intradialytic Hypotension during Hemodialysis. (1st December 2006) - Giaime, Philippe; Carrega, Louis; Fenouillet, Emmanuel; Mercier, Laurence; Gerolami, Victoria; Ruf, Jean; Sauze, Nicole; Brunet, Philippe; Saadjian, Alain; Berland, Yvon; Dussol, Bertrand; Guieu, Regis
Abstract : Background: Intradialytic hypotension (IDH) is a common complication of hemodialysis sessions (HDSs). Adenosine may contribute to the drop in blood pressure during IDH events because it has hypotensive effects. As A2A adenosine receptor expression is essential for blood pressure control, we compared the expression of A2A receptors (Bmax, KD, and messenger ribonucleic acid [mRNA] levels) in peripheral blood mononuclear cells from IDH and non-IDH patients and from controls. We also evaluated adenosine plasma levels (APLs). Methods: We included 10 hemodialyzed patients with at least three IDH events per month. We also included 11 hemodialyzed patients with no history of IDH events and 10 healthy subjects as controls. Results: IDH patients had higher Bmax values than non-IDH patients (mean before HDS, +86%; after HDS, +112%), whereas non-IDH patients had lower Bmax values than controls (mean −72%). KD values were not significantly different between patients and controls. The levels of mRNA increased significantly during HDS but without an increase in receptor expression on the cell membranes. APLs were higher in hemodialyzed patients than in controls. Conclusion: We found that A2A receptors are more expressed in IDH patients than in non-IDH patients, whereas APL was high in all patients. Both high APL and a relative increase in A2A receptor expression may favor IDH events.